COVID-19 Impact Monitoring : Malawi, Round 2 - Malawi National Statistical Office (World Bank, Washington, DC, 2020)
In May 2020, the National Statistical Office (NSO), with support from the World Bank, launched the High-Frequency Phone Survey on COVID-19 (HFPS COVID-19), a monthly survey of a nationally representative sample of households previously interviewed as part of the Malawi Integrated Household Panel Survey to monitor the economic impact of the pandemic and other shocks. This brief presents findings of the second round of the Malawi HFPS COVID-19 conducted in July 2020.